Alkaloids content, cytotoxicity and anti-Toxoplasma gondii activity of Psidium guajava L. and Tinospora crispa - Lee, Wei Cai; Mahmud, Roziahanim; Noordin, Rahmah; Piaru, Suthagar Pillai; Perumal, Shanmugapriya; Ismail, Sabariah (Bangladesh Journal of Pharmacology, 2012)
The alkaloids content, cytotoxicity activity and anti-parasitic activity of Tinospora crispa Miers and Psidium guajava L. against parasite Toxoplasma gondii were investigated. Both of the crude plant extracts contained high amount of crude alkaloids and were not toxic to Vero cells (EC50 >100 µg/mL). Following non-toxicity finding of the extracts, the in vitro anti-parasitic assay was carried out with clindamycin served as the positive control. T. crispa stem crude extract with EC50 value of 7.71 ± 1.56 µg/mL, showed potential anti-T. gondii activity as the results were comparable to clindamycin (EC50 = 6.24 ± 0.53 µg/mL). These findings suggest that stem extract of T. crispa Miers contained some potential active compounds against Toxoplasma gondii. Selective important alkaloids in the T. crispa stem fractions may be the key factor for their anti-parasitic activity. Further study is being carried out to investigate for potential bioactives present in the T. crispa extract through bioactivity guided fractionation.